P49 Modifying health promotion interventions for ethnic minority groups: systematic review of empirical evidence. (16th November 2010) - Liu, J J; Davidson, E; Bhopal, R; Johnson, M; White, M; Deverill, M; Netto, G; Sheikh, A
Abstract : Background: Health promotion interventions have proved to be cost-effective strategies to reduce morbidity and mortality associated with smoking, physical inactivity and poor diet in the general population. Some ethnic minority groups are disproportionately affected by these lifestyle factors, and existing evidence suggests that adapting evidence-based health promotion interventions for these populations may prove to be an effective strategy to tackle health inequalities. Objectives: To identify health promotion interventions for smoking cessation, increasing physical activity and improving nutrition which have been adapted for African-Caribbean, South Asian and Chinese-origin populations and to document how this has been achieved and with what effect. Design: A systematic review was conducted with two reviewers independently searching, identifying, extracting and critically appraising empirical studies of adapted interventions. The databases searched include MEDLINE, EMBASE, ASSIA, Psycinfo, CINAHL, BIOSIS, Cochrane, ISI Web of Science, Lilacs, Campbell and SCEH. Results: In total, 48 740 records were identified. 95 empirical studies were identified as relevant and included in the analysis. The majority of adapted intervention studies took place in the USA, conducted with African-Caribbean origin populations and these predominantly involved women. All studies conducted with Chinese-origin populations took place in the USA while the majority of studies with South Asian-origin populations were conducted in the UK. Multi-component interventions targeting physical activity and nutrition were the most common followed by smoking cessation interventions. Interventions utilised a variety of adapted methods, resources and/or settings. The components of the adaptation process identified include methods such as ethnically matching programme facilitators; subsidising gym memberships and promoting low-cost alternatives to usual exercise options. Resources include culturally targeting materials (eg, using ethnic actors in videos and including photos of foods commonly consumed by the population in promotional material); utilising existing community resources (eg, religious leaders) and accommodating for differing linguistic and language competencies. Settings include holding interventions in familiar locations and utilising culturally appropriate scenarios to elicit behaviour change. Conclusions: A large body of evidence exists for adapted interventions. Identification of the components involved in the adaptation process for ethnic minority populations is a critical step for building on existing adaptation principles. Furthermore, this study will enable the development of a framework to guide the adaptation of mainstream evidence-based guidelines to be salient for different populations and contexts.